2005
DOI: 10.1002/humu.9337
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic diabetes insipidus caused by mutation of Tyr205: A key residue of V2 vasopressin receptor function

Abstract: Mutations in the V2 vasopressin receptor (AVPR2) are the most frequent genetic cause of the inherited nephrogenic diabetes insipidus (NDI). About 50% of all missense mutations found in extracellular loops of AVPR2 introduce additional cysteine residues, e.g. R181C, G185C, and Y205C. To explain the loss of receptor function two mechanistic models were suggested: First, the introduction of an additional extracellular Cys residue disrupts the conserved disulfide bond connecting the first and the second extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The sister was heterozygous for the 12 bp-deletion mutation. This deletion of 4 amino acids (Arg-247 to Gly-250) has been previously described and it was suggested that it does not cause effects on receptor function [25] . Having 1 X chromosomal allele mutated in a female, it usually causes symptom of mild NDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sister was heterozygous for the 12 bp-deletion mutation. This deletion of 4 amino acids (Arg-247 to Gly-250) has been previously described and it was suggested that it does not cause effects on receptor function [25] . Having 1 X chromosomal allele mutated in a female, it usually causes symptom of mild NDI.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid correction of hypernatremia may also predispose these patients toward seizures and cerebral edema [14][15][16] . Severe dehydration and hypernatremia in congenital NDI are avoided by offering free access to water, while urine output can partially be reduced by a combination of treatments including low-salt and low-protein diet, hydrochlorothiazide (HCTZ)-amiloride, and non-steroidal anti-inflammatory drugs [17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…cAMP content of cell extracts was determined by a non-radioactive cAMP accumulation assay based on the ALPHAScreenä technology according to the manufacturer's protocol (Perkin Elmer LAS, Rodgau-Jügesheim, Germany) [26]. Stimulation with various AVP concentrations ([Arg8]vasopressin acetate salt, Sigma-Aldrich, Seelze, Germany) was performed 48 h after transfection for 1 h at 37°C.…”
Section: Alphascreenä Camp Assaymentioning
confidence: 99%
“…On the basis of available sequence data for validated P2Y receptors, key residues were extracted to define P2Y 12 -like and P2Y 1 -like receptor groups [ 11 , 38 , 39 ]. In recent studies, we have shown for several GPCR that a significant number of orthologs is required for identification of functional motifs and key residues [ 33 , 40 42 ]. By mining public databases and by amplifying and sequencing P2Y 12 -like orthologs we have acquired large sets of sequences of P2Y 12 (74 orthologs), P2Y 13 (31 orthologs), P2Y 14 (38 orthologs), GPR87 (51 orthologs), GPR171 (41 orthologs), GPR82 (34 orthologs), and GPR34 (133 orthologs) to determine structural conservation of the members and to identify amino acid sequence motifs and key residues that are unique for the P2Y 12 -like receptor group and the individual members (Fig.…”
Section: Structural Evolution Of P2y 12 -Like Gpcrmentioning
confidence: 99%